Investigation of shear stress with experimental study and CFD simulation of free surface flows on round shaped solid moving object (Journal of Naval Architecture and Marine Engineering, 2023)
This paper presents a comprehensive study based on the results of a series of experiments conducted at different flow rates using micro-thinned sensors to obtain shear stress and velocity components around solid moving objects.  The object dynamically represents marine  vehicles  and  inflating  boats  through  simplifications  that ignore the effect of air in the object due to the complexity of capturing the viscoelastic behavior of such vehicles in  simulations.  Data obtained  from  experiments  are  compared  with  CFDsimulation  results  to  observe  the accuracy  and  impact  of  flow  rate  on  different  weights.  The simulation uses the  Reynolds-averaged  Navier–Stokes  formulation  with  the  VOF  method  and  the  turbulence  models  SST  k-ω. Three-dimensional transient simulations are performed using the overset grid technique to define the motion of the solid object in the flow field.  Uncertainty analysis  was  carried  out  for  both  experiments  and  CFD  simulations.  The obtained shear stress  and  velocity  results  in  the  simulations  are  valid  and  acceptable  for  different  flow  rates  on  various weights. It is also concluded and demonstrated that weight has a specific impact on the shear stress and motion of the object.Journal of Naval Architecture and Marine Engineering, December, 2023, P: 53-76